Sports Technology Research at University of Tsukuba - Asai, T. (5. Asia-Pacific Congress on Sport Technology 2011 Melbourne, 2011)
This Multi Support Project could be continued until Sochi Olympic Games (2014) (may be until Rio de Janeiro Olympic Games (2016) and more) Today, Sports Technology is really critical, if country wins the gold medal, they will need the Sports Technology together with athletes for the best chance to succeed.